Analisis Komparatif Kinerja Keuangan Sebelum Dan Selama Pandemi Covid-19 Dan Dampaknya Terhadap Harga Saham : (Studi Kasus Pada Sektor Perbankan Syariah Yang Terdaftar Pada ISSI) - Wilda Yulia Rusyida; Yeyen Fitri Setyaningrum (UIN K.H. Abdurrahman Wahid Pekalongan, 2022)
The impact of the COVID-19 pandemic has reduced sectors in the economy and finances. The banking world has also been affected by the COVID-19 pandemic. Therefore, the purpose of this study is to find out whether the COVID-19 pandemic causes changes in the financial performance of banks listed on ISSI and their share prices. Financial performance is a form of accountability of a company to the owners of capital in which it shows several financial statements as an illustration of how the company's performance in generating profits / profits. This research is a type of quantitative research. Sources of data used are secondary data where the financial statements of each bank to be studied can be obtained from the website of each company. The sampling technique is purposive sampling. This study uses classical assumption test data analysis and hypothesis testing (Simultaneous F Test), as well as a comparative test to compare performance before and during the COVID-19 pandemic using SPSS version 22. The results show that there are differences in financial performance using the NPF ratio ( Non Performing Finance), FDR (Financing Deposit to Ratio), ROE (Retrun On Equit), and BOPO (Operating Expenses to Operating Income) between before and during the covid-19 pandemic and financial performance using this ratio has an impact on stock prices